73.9k views
5 votes
Multiply. (2x2 + 4x - 3)(x2 - 2x + 5)

2 Answers

2 votes
For a moment, let
y=x^2-2x+5. Then by the distributive property,


(2x^2+4x-3)p=2x^2p+4xp-3p


Again by the distributive property,


2x^2p=2x^2(x^2-2x+5)=2x^4-4x^3+10x^2


4xp=4x(x^2-2x+5)=4x^3-8x^2+20x


-3p=-3(x^2-2x+5)=-3x^2+6x-15

Taking everything together, we get


(2x^2+4x-3)(x^2-2x+5)=(2x^4-4x^3+10x^2)+(4x^3-8x^2+20x)+(-3x^2+6x-15)

(2x^2+4x-3)(x^2-2x+5)=2x^4-x^2+26x-15
User BlackMael
by
4.6k points
2 votes

Answer:

the answer is C

Explanation:

got it right on the assignment

User KostaZ
by
5.4k points